PENINGKATAN PELAYANAN MASYARAKAT MELALUI INOVASI APLIKASI DIGITAL: STUDI KASUS IMPLEMENTASI SURADI DI KANTOR KELURAHAN KESATRIAN, KECAMATAN BLIMBING, KOTA MALANG - Hadiwiyono, Hadiwiyono; Soeltanto, Taufiq; Rulliansyah, Iqbal (JOURNAL AKSES STIA MALANG, 2024)
This research explores the impact and effectiveness of implementing the "SURADI" digital application at the Kesatrian Subdistrict Office, Blimbing District, Malang City in improving community services. With a focus on innovation in government administration, this study uses a case study approach to examine how these digital applications have accelerated administrative processes, minimized data input errors, and increased the affordability of services for the public. Data was collected through interviews, observation and document analysis. The research results show that the implementation of SURADI has had a positive impact in increasing the efficiency of public services. However, challenges such as limited internet access and technological understanding among the public are obstacles to the effective use of this application. Thus, this research concludes the need for socialization, training and improvement of technological infrastructure to ensure the successful implementation of digital applications in improving community services at the local level